The Effect of Family Support and Self-Efficacy on Housewives' Entrepreneurial Interest Through Training Access in Depok City - Andreas Satya Pratama Kurniawan; Osly Usman (Journal of Digital Business and Global Economy, 2026)
This research examines how family support and self-efficacy influence the entrepreneurial aspirations of housewives in Depok City, where access to training is a mediating variable. Employing quantitative explanatory survey methodology with Partial Least Square-Structural Equation Modeling (PLS-SEM) through SmartPLS, stratified random sampling within five sub-districts was employed with 100 respondents. Results indicate that family support significantly influences training access (β = 0.339, p < 0.01), while self-efficacy significantly affects both training access (β = 0.510, p < 0.01) and entrepreneurial interest (β = 0.390, p < 0.01). The strongest predictor of entrepreneurial interest was training access (β = 0.486, p < 0.01). Family support has no direct impact on entrepreneurial interest, but it is fully mediated through training access (β = 0.164, p < 0.05). Self-efficacy partially mediates through training access (β = 0.248, p < 0.01). This model accounts for 34.4% and 55.9% of variance in entrepreneurial interest and training access respectively. The following findings emphasize that self-efficacy and training access are significant determinants of entrepreneurial interest, whereas family support works through some indirect mechanism. Policy considerations highlight the demand for flexible and accessible training and self-efficacy development programs aimed at housewives in the urban Indonesian context.